1991
DOI: 10.1007/bf01313510
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of larval development and growth of the sea cucumberActinopyga echinites: Ovary-induced ova and DTT-induced ova

Abstract: Abstract. Adult Actinopyga echinites (Jaeger) were collected from northern Taiwan in September 1989. Oocytes were induced to mature by bathing them in ovary juice (ovary-induced ova) or in 10-2 M dithiothreitol (DTTinduced ova). The percentage of germinal vesicle breakdown (GVBD) increased from 0.4 to 6.4% in the former treatment and to 84% in the latter. After artificial fertilization, the embryos were cultured in seawater (3 5%o S) at 25 to 28 °C. Larvae were fed with the alga Isochysis aff. galbana at 10 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Reisener 1976, Weber 1980, Weete 1980, and the larvae of many marine invertebrates (e.g. Richmond 1987, Chen et al 1991, Harms et al 1991, Ouellet et al 1992). Because of their high caloric value, neutral lipids constitute an important endogenous energy source that can fuel a host of energy demanding activities including motility, germination, metamorphosis, and growth.…”
mentioning
confidence: 99%
“…Reisener 1976, Weber 1980, Weete 1980, and the larvae of many marine invertebrates (e.g. Richmond 1987, Chen et al 1991, Harms et al 1991, Ouellet et al 1992). Because of their high caloric value, neutral lipids constitute an important endogenous energy source that can fuel a host of energy demanding activities including motility, germination, metamorphosis, and growth.…”
mentioning
confidence: 99%
“…This may influence spawning in the presence of other stimuli at different times during the reproductive season. For RNE to be effective, it must act on the follicle cell, which produces a second compound that induces GVBD in the oocyte (Strathmann and Sato 1968;Maruyama 1980Maruyama , 1985Chen et al 1991). It has also been shown that the oocyte produces an inhibitor that prevents GVBD until spawning occurs (Smiley and Cloney 1985;Giese and Kanatani 1987;Eckelbarger and Young 1992).…”
Section: Germinal Vesicle Breakdownmentioning
confidence: 99%
“…In indirectly developing species, the developmental stages of holothuroid larvae are known as auricularia, doliolaria and pentactula. Some examples of indirectly developing species include Aspidochirotida: Holothuroidea: Actinopyga echinites (Chen et al 1991), Holothuria scabra (James 2004) and Holothuria leucospilota (Hiratsuka and Uehara 2009); and Aspidochirotida: Stichopodidae: Stichopus californicus (Smiley 1986), A. japonicus (Yoshida et al 2002), Australostichopus mollis (Morgan 2008b) and Isostichopus fuscus (Mercier et al 2004). This developmental style is characterized by an auricularia larval stage of feeding on plankton.…”
Section: Introductionmentioning
confidence: 98%